Traumatic Spinal Cord Injury Due to Horse Riding Accident in A Patient with Klippel-Feil Syndrome: A Case Report - Christy Angeline; Hendra, Debora; Maria, Rani; Maulana Siahaan, Denny (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Spinal cord injury is a severe medical illness that frequently leaves patients permanently disabled and with severe morbidity. In some cases, sports may be one of the factors causing spinal cord injuries, like horse riding. Anatomical variation in the vertebra may become a potential risk factor for an injury such as Klippel-Feil syndrome. Case: A 30-year-old female came to the emergency room after falling while riding a horse. The patient complained of not being able to move her hands and feet and feeling numb from the neck area to the feet. X-rays of the cervical spine showed an anatomical variation in fusion at the C4 and C5 vertebrae, known as Klippel-Feil syndrome. No visible fracture or dislocation was found. The MRI results showed intramedullary lesions at the C3 to C5 vertebral bodies level and compression fracture of the C4-C5 vertebral body accompanied by narrowing of the C4-C5 intervertebral disc. Discussion: Patients with Klippel-Feil syndrome may be more vulnerable to transient neurologic deficits after minor trauma. The fused segments' altered mechanical force transfer, which results in the adjacent non-fused segments moving excessively, is most likely related to this. Conclusion: Serious medical conditions like spinal cord injuries often leave victims severely sick and permanently incapacitated. Sports such as horse riding are associated with traumatic spinal cord injuries. Patients with Klippel-Feil syndrome may be more susceptible to this trauma.